The gain-of-function UBE3A Q588E variant causes Angelman-like neurodevelopmental phenotypes in mice - Kellan P. Weston; Anna M. Gunelson; Susan E. Maloney; Xia Ge; Jalin A. Stelzer; Kwang-Soo Kim; Shylyn Collier; Marissa M. Mindt; Megan J. Agajanian; Michael B. Major; Dennis Goldfarb; Kevin K. Noguchi; et al. (Scientific Reports)
Abstract Mutations in the E3 ubiquitin ligase UBE3A that cause enzymatic gain-of-function result in disease phenotypes which differ from classic Angelman syndrome. However, these phenotypes are highly heterogeneous raising questions about the mechanistic basis of such phenotypic diversity. Here, we characterize a mouse model harboring a Ube3a Q606E gain of function variant (UBE3A Q588E in humans). Extensive behavioral phenotyping showed that animals possessing a maternally inherited mutation (Ube3a mQ606E) paradoxically show many behavioral deficits indicative of overall UBE3A loss-of-function. These included pronounced motor deficits, hypoactivity, and reduced stereotypic behaviors. Moreover, brain weights and MRI analysis revealed global microcephaly with a postnatal onset, consistent with phenotypes described in Angelman syndrome model mice. Additional biochemical analyses demonstrated an increased abundance of UBE3A substrates in brain tissue and immunofluorescence analyses showed that microcephaly is not caused by increased apoptotic cell death. Together, our results strongly suggest a novel mechanism by which the Ube3a mQ606E mutation leads to enhanced self-targeted degradation of UBE3A, leading to an overall loss of enzyme activity, resulting in Angelman-like phenotypes in vivo.